PROFIL PENDERITA KANDIDIASIS KUTIS DI POLIKLINIK KULIT DAN KELAMIN RSUD ULIN BANJARMASIN PERIODE 2017-2021 - Saida, Noorsabila; Hadi, Sukses; Sanyoto, Didik Dwi; Essary, Erika Dewi; Wydiamala, Erida (Homeostasis, 2024)
Abstract: Cutaneous candidiasis is a skin infection caused by the Candida fungus. Various predisposing factors for candidiasis include low environmental hygiene, high levels of humidity, poor ventilation, and the presence of comorbidities in sufferers that weaken the immune system. This research aims to find out the profile of cutaneous candidiasis sufferers in the Skin and Venereology Polyclinic at RSUD Ulin Banjarmasin for the 2017 - 2021 period. This research method is descriptive observational using medical records and electronic data. The results of this study show that the total number of cases of cutaneous candidiasis was 123 patients, with the most cases occurring in 2017 (32.5%). Women accounted for the majority of cases (65,9%) and the largest age group was 0 - 5 years (35.0%). Most of the patients came from the Banjarmasin area (65,0%) and most jobs are unemployed (35.8%). The most common classification (location of lesions) is intertriginous (60.2%) and the most common type of treatment is topical (58,5%). The conclusion of this study is that the number of cases for the 2017 - 2021 period was 123 patients, the most cases were in 2017, gender was female, age range 0 - 5 years, came from the Banjarmasin area, jobs are unemployed, location of the lesion was intertriginous, and type of treatment topical antifungal. Keywords: cutaneous candidiasis, fungal infections, Candida, Ulin Hospital Abstrak: Kandidiasis kutis ialah infeksi pada kulit yang disebabkan oleh jamur Candida. Berbagai faktor predisposisi penyakit kandidiasis antara lain faktor rendahnya higienitas lingkungan, tingginya tingkat kelembaban, ventilasi yang kurang, dan adanya penyakit penyerta dari penderita yang melemahkan sistem kekebalan tubuh. Peneltian ini bertujuan untuk mengetahui bagaimana profil penderita kandidiasis kutis di Poliklinik Kulit dan Kelamin RSUD Ulin Banjarmasin periode 2017 - 2021. Metode penelitian ini ialah observasional deskriptif dengan menggunakan rekam medis dan data elektronik. Hasil penelitian ini menunjukkan total keseluruhan kasus kandidiasis kutis adalah 123 pasien, dengan kasus terbanyak terjadi di tahun 2017 (32,5%). Perempuan jadi kasus terbanyak (65,9%) dan kelompok usia terbanyak ialah 0 - 5 tahun (35,0%). Sebagian besar pasien berasal dari daerah Banjarmasin (65,0%) dan pekerjaan terbanyak adalah tidak bekerja (35,8%). Klasifikasi (lokasi lesi) tersering ialah di intertriginosa (60,2%) dan jenis pengobatan terbanyak ialah topikal (58,5%). Kesimpulan penelitian ini adalah jumlah kasus periode 2017 - 2021 sebanyak 123 pasien, kasus terbanyak ada di tahun 2017, jenis kelamin perempuan, rentang usia 0 - 5 tahun, berasal dari daerah Banjarmasin, pekerjaan tidak bekerja, lokasi lesi di intertriginosa, dan jenis pengobatan antijamur topikal. Kata-kata kunci: kandidiasis kutis, infeksi jamur, Candida, RSUD Ulin